Leather glass as well as preparation method and application thereof

By using leather glass with high content of SiO2, PbO, Bi2O3 and other oxides in the microchannel plate, its baking temperature and acid resistance are improved, and the low baking temperature and ion resistance of microchannel plates in the prior art are solved. The problem of large feedback effect has achieved efficient resistance reduction and performance improvement.

CN119263630APending Publication Date: 2025-01-07CHINA BUILDING MATERIALS ACADEMY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411551549.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing microchannel plates (MCPs) have low baking temperature and large ion feedback effects, and the softening temperature, thermal stability and acid resistance of the leather glass are insufficient, which cannot meet the requirements of high-temperature baking and acid etching.

Method used

Using a leather glass containing SiO2, PbO, Bi2O3, Cs2O, Rb2O, BaO, MgO, Al2O3, ZrO2 and SrO, by controlling the content and proportion of each component, the glass phase transition temperature, softening temperature and thermal expansion of the glass are increased. The coefficient is adopted, and the preparation method of high temperature melting and mechanical extrusion molding is used to prepare microchannel plates with high baking temperature and low body resistance.

Benefits of technology

The baking temperature of the microchannel plate is increased to ≥580℃, and the body resistance is ≤172MΩ. It has good crystallization resistance and acid resistance stability, which significantly reduces the ion feedback effect, extends the service life and improves the signal-to-noise ratio. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263630A_ABST
    Figure CN119263630A_ABST
Patent Text Reader

Abstract

The invention relates to leather glass as well as a preparation method and application thereof, and the leather glass comprises the following components in terms of oxide: SiO2, PbO, Bi2O3, Cs2O, Rb2O, BaO, MgO, Al2O3, ZrO2, Nb2O5 and SrO. Wherein the content of the SiO2 is 20 to 40 weight percent; the total content of the PbO and the Bi2O3 is 35 to 45 weight percent; the total content of the Cs2O and the Rb2O is 5 to 12 weight percent; the total content of the BaO and the MgO is 10 to 16 weight percent; the content of the Al2O3 is 1 to 4 weight percent; the total content of the ZrO2 and the Nb2O5 is 3 to 7 weight percent; the content of the SrO is 5 to 10 weight percent. The glass phase transition temperature Tg of the leather glass is larger than or equal to 620 DEG C, the softening temperature Tf of the leather glass is larger than or equal to 680 DEG C, the thermal expansion coefficient of the leather glass at the temperature of 20-300 DEG C is (67-72) * 10 <-7 > / DEG C, the leather glass has good devitrification resistance and acid-resistant stability, and further, the baking-resistant temperature of the microchannel plate prepared from the leather glass is larger than or equal to 580 DEG C, and the bulk resistance of the microchannel plate is smaller than or equal to 172 megohms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of optoelectronic materials, and in particular relates to leather glass and a preparation method and application thereof. Background Art

[0002] Microchannel plate (MCP) is an excellent two-dimensional electron multiplying material. It is the core material of extremely weak photoelectric detection devices such as image intensifiers, photomultiplier tubes, and photon counting tubes. It has the characteristics of high gain, high spatial resolution, and high temporal resolution. It has very important applications in high-energy physics, radiation diagnosis and treatment, space detection, ultraviolet detection, and other fields.

[0003] When the microchannel plate is working, the incident electrons enter the microchannel plate and, after multiple electron multiplications, form a high-density electron cloud at the exit of the microchannel plate. The electron cloud will ionize with the residual gas inside the microchannel plate (such as N2, H2, CO2 and CO, etc.), causing the positive ions between the plates to move in the opposite direction under the action of the electric field, bombarding the photocathode in the reverse direction, causing damage to the photocathode and generating interference signals, reducing the service life and signal-to-noise ratio of the microchannel plate.

[0004] At present, the baking temperature of MCP in the prior art is low, and a large number of residual gas molecules adsorbed on the inner wall surface of the channel cannot be removed by high-temperature baking, which easily leads to ion feedback effect. In addition, the softening temperature, thermal stability, acid resistance stability and anti-crystallization performance of the skin glass used to prepare MCP in the prior art need to be optimized so that the various properties of the skin glass can meet the special requirements of the preparation and use of microchannel plates. Summary of the invention

[0005] The main purpose of the present invention is to provide a leather glass and its preparation method and application. The technical problem to be solved is to overcome the shortcomings of the microchannel plate (MCP) in the prior art, such as low baking temperature and large ion feedback effect, and to effectively improve its baking temperature and reduce its ion feedback effect. At the same time, the glass phase transition temperature T g ≥620℃, softening temperature T f ≥680℃, the thermal expansion coefficient at 20~300℃ is (67~72)×10 -7 / ℃, and has good anti-crystallization performance and acid resistance stability. Furthermore, the microchannel plate prepared from the leather glass has a baking temperature of ≥580℃ and a body resistance of ≤172MΩ.

[0006] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical solutions. According to the present invention, a leather glass, in terms of oxides, includes SiO2, PbO, Bi2O3, Cs2O, Rb2O, BaO, MgO, Al2O3, ZrO2, Nb2O5 and SrO;

[0007] Among them, the content of SiO2 is 20-40wt%; the total content of PbO and Bi2O3 is 35-45wt%; the total content of Cs2O and Rb2O is 5-12wt%; the total content of BaO and MgO is 10-16wt%; the content of Al2O3 is 1-4wt%; the total content of ZrO2 and Nb2O5 is 3-7wt%; the content of SrO is 5-10wt%.

[0008] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.

[0009] Preferably, the aforementioned skin glass, wherein the content of SiO2 is 22-28wt%; the total content of PbO and Bi2O3 is 38-42wt%; the total content of Cs2O and Rb2O is 7-10wt%; the total content of BaO and MgO is 12-14wt%; the content of Al2O3 is 2-3wt%; the total content of ZrO2 and Nb2O5 is 3-6wt%; the content of SrO is 6-9wt%.

[0010] Preferably, in the aforementioned skin glass, the weight ratio of the PbO to the Bi2O3 is 4 to 9:1.

[0011] Preferably, in the aforementioned skin glass, the weight ratio of the total content of the PbO and the Bi2O3 to the content of the SiO2 is 1:0.3 to 0.9.

[0012] Preferably, in the aforementioned skin glass, the weight ratio of the content of Al2O3 to the total content of SiO2, Cs2O and Rb2O is 1:10-14.

[0013] Preferably, in the aforementioned skin glass, the weight ratio of the total content of the SrO and the Al2O3 to the content of the SiO2 is 1:2-5.

[0014] The purpose of the present invention and the technical problems solved by the present invention are also achieved by the following technical solutions. According to a method for preparing a leather glass proposed by the present invention, the method comprises the following steps: (1) first melting raw materials and a clarifier to obtain pre-sintered clinker glass, wherein the raw materials include SiO2, PbO, Bi2O3, Cs2O, Rb2O, BaO, MgO, Al2O3, ZrO2, Nb2O5 and SrO in terms of oxides;

[0015] (2) performing a second melting and clarification on the pre-sintered clinker glass to obtain sintered clinker glass;

[0016] (3) Extruding the sintered clinker glass to obtain a leather glass tube;

[0017] (4) Annealing the leather glass tube.

[0018] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.

[0019] Preferably, in the aforementioned preparation method, the temperature of the first melting is 1300-1400°C.

[0020] Preferably, in the aforementioned preparation method, the temperature of the second melting is 1550-1600°C.

[0021] Preferably, in the aforementioned preparation method, the heating rate of the annealing treatment is 2.5-4.0°C / min.

[0022] Preferably, in the aforementioned preparation method, the cooling rate of the annealing treatment is 0.5-1.5°C / h.

[0023] The purpose of the present invention and the technical problems solved by the present invention are also achieved by the following technical solutions: A microchannel plate proposed in the present invention comprises the leather glass as described above, or the leather glass prepared by the preparation method as described above.

[0024] By means of the above technical solution, the leather glass and its preparation method and application of the present invention have at least the following advantages:

[0025] (1) In the present invention, the glass transition temperature T g ≥620℃, softening temperature T f ≥680℃, based on this, the baking temperature of the microchannel plate prepared from the leather glass is ≥580℃.

[0026] (2) In the present invention, the thermal expansion coefficient of the leather glass at 20-300°C is (67-72)×10 -7 / ℃, has good thermal stability.

[0027] (3) In the present invention, the leather glass has no crystallization and phase separation at 750-1100°C and has good anti-crystallization performance.

[0028] (4) In the present invention, the acid dissolution rate of the leather glass is less than 0.01 mg / (cm 2 ×min), and the acid resistance stability reaches level 1.

[0029] (5) In the present invention, the volume resistance of the microchannel plate prepared from the leather glass is ≤172 MΩ, which can significantly reduce the volume resistivity of the microchannel plate and expand the dynamic range of the microchannel plate.

[0030] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a 400-fold actual image of the microchannel plate microscope of Example 1 of the present invention.

[0032] Figure 2 This is a 400-fold actual image of the microchannel plate microscope of Example 2 of the present invention. DETAILED DESCRIPTION

[0033] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of the leather glass and its preparation method and its specific implementation, structure, characteristics and effects of the application according to the present invention in combination with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments can be combined in any suitable form.

[0034] The first aspect of the present invention provides a leather glass, which includes SiO2, PbO, Bi2O3, Cs2O, Rb2O, BaO, MgO, Al2O3, ZrO2, Nb2O5 and SrO in terms of oxides;

[0035] Among them, the content of SiO2 is 20-40wt%; the total content of PbO and Bi2O3 is 35-45wt%; the total content of Cs2O and Rb2O is 5-12wt%; the total content of BaO and MgO is 10-16wt%; the content of Al2O3 is 1-4wt%; the total content of ZrO2 and Nb2O5 is 3-7wt%; the content of SrO is 5-10wt%.

[0036] The inventors found that the various components of the leather glass interact with each other and jointly determine the various properties of the leather glass.

[0037] Among them, SiO2 is the basic skeleton structure of the leather glass. The present invention limits the content of SiO2 to 20-40wt%. By controlling the content of SiO2 to meet the above range, the strength, chemical stability, glass viscosity and thermal expansion coefficient of the leather glass can be maintained. When the SiO2 content is lower than 20wt%, the chemical stability of the leather glass will be deteriorated; when the SiO2 content is higher than 40wt%, the viscosity of the leather glass will increase and the expansion coefficient will be too low. The high-temperature viscosity of the leather glass is very large, and the melting temperature requirement is relatively high. At the same time, the leather glass is prone to defects such as sand and stone.

[0038] PbO and Bi2O3 are intermediates of the leather glass. On the one hand, they can significantly reduce the clarification temperature of the leather glass during melting, which is beneficial to improving the leather glass material properties and convenient for drawing into glass tubes. On the other hand, lead and bismuth are variable valence elements. In the hydrogen reduction process of preparing a microchannel plate with leather glass, under the action of hydrogen, their high-valent ions are reduced to lead atoms and bismuth atoms. The reduced lead and bismuth atoms gather together, which can significantly reduce the volume resistivity of the microchannel plate and expand the dynamic range of the microchannel plate. The present invention limits the total content of PbO and Bi2O3 to 35-45wt%. By controlling the total content of PbO and Bi2O3 to meet the above range, part of PbO and Bi2O3 can enter the silicon oxygen network skeleton of the leather glass, which plays a role in adjusting the expansion coefficient, softening temperature, refractive index and other properties. When the total content of PbO and Bi2O3 is lower than 35wt%, it is difficult to control the volume resistivity of the microchannel plate to an appropriate range; when the total content of PbO and Bi2O3 is higher than 45wt%, it is not conducive to ensuring the stability of the skin glass and deteriorates the glass-forming properties of the skin glass.

[0039] Cs2O and Rb2O are structurally regulating oxides of the skin glass, which can replace elements such as potassium and sodium with small ion radius and easy to produce ion feedback effect. The present invention limits the total content of Cs2O and Rb2O to 5-12wt%. By controlling the total content of Cs2O and Rb2O to meet the above range, the thermal properties such as the expansion coefficient and softening temperature of the skin glass can be improved, the secondary electron emission coefficient of the skin glass can be maintained, and the melting difficulty can be appropriately reduced. When the total content of Cs2O and Rb2O is less than 5wt%, the gain of the microchannel plate will be significantly reduced; when the total content of Cs2O and Rb2O exceeds 12wt%, the chemical stability, structural stability and acid corrosion resistance of the skin glass will be reduced, and it is not conducive to improving the baking temperature resistance of the microchannel plate.

[0040] BaO and MgO are the outer oxides of the glass network of the leather glass, and are also fluxes. They enter the vacancies between the leather glass skeletons to adjust the viscosity and expansion coefficient of the leather glass. The present invention limits the total content of BaO and MgO to 10-16wt%. By controlling the total content of BaO and MgO to meet the above range, the material properties of the leather glass can be improved, which is beneficial to the molding operation and thermal processing of the leather glass. When the total content of BaO and MgO is less than 10wt%, the viscosity and expansion coefficient of the leather glass cannot meet the use requirements; when the total content of BaO and MgO is greater than 16wt%, the crystallization tendency of the leather glass will increase, which is not conducive to the later plate making.

[0041] Al2O3 is a glass structure regulating oxide of the skin glass. The present invention limits the content of Al2O3 to 1-4wt%. By controlling the content of Al2O3 to meet the above range, the thermal expansion coefficient and acid corrosion resistance of the skin glass can be significantly affected. When the content of Al2O3 is less than 1%, the chemical stability and thermal stability of the skin glass will be reduced; when the content of Al2O3 is higher than 4%, the melting temperature of the skin glass will be significantly increased, causing melting difficulties.

[0042] ZrO2 and Nb2O5 are the outer oxides of the glass network of the leather glass, and are also oxides with high softening points. The present invention limits the total content of ZrO2 and Nb2O5 to 3-7wt%. By controlling the total content of ZrO2 and Nb2O5 to meet the above range, the softening temperature of the leather glass can be increased, and the baking resistance temperature of the microchannel plate can be significantly improved, so that it can be baked at high temperature to remove a large number of residual gas molecules adsorbed on the inner wall of the channel, and reduce the ion feedback effect. When the total content of ZrO2 and Nb2O5 is lower than 3wt%, it is not conducive to increasing the softening temperature of the leather glass, and it is not conducive to increasing the baking resistance temperature of the microchannel plate; when the total content of ZrO2 and Nb2O5 is higher than 3wt%, the performance of the leather glass will deteriorate, and phase separation will occur.

[0043] SrO is an oxide outside the glass network of the skin glass and is also an oxide with a high secondary electron emission coefficient. The present invention limits the content of SrO to 5-10wt%. By controlling the content of SrO to meet the above range, the gain of the microchannel plate can be significantly improved to ensure its performance. When the content of SrO is lower than 5wt%, it is not conducive to improving the gain of the microchannel plate; when the content of SrO is higher than 10wt%, it will increase the difficulty of melting the skin glass and deteriorate the glass forming performance.

[0044] Therefore, the components of the leather glass, SiO2, PbO, Bi2O3, Cs2O, Rb2O, BaO, MgO, Al2O3, ZrO2, Nb2O5 and SrO, interact with each other and jointly determine the glass phase transition temperature T of the leather glass. g≥620℃, softening temperature T f ≥680℃, the thermal expansion coefficient at 20~300℃ is (67~72)×10 -7 / ℃, has good anti-crystallization performance and acid resistance stability. Furthermore, the microchannel plate prepared from the leather glass has a baking temperature of ≥580℃ and a body resistance of ≤172MΩ.

[0045] According to a specific embodiment of the present invention, the content of SiO2 is 22-28wt%; the total content of PbO and Bi2O3 is 38-42wt%; the total content of Cs2O and Rb2O is 7-10wt%; the total content of BaO and MgO is 12-14wt%; the content of Al2O3 is 2-3wt%; the total content of ZrO2 and Nb2O5 is 3-6wt%; the content of SrO is 6-9wt%.

[0046] Therefore, the properties of leather glass can be further optimized to make its glass phase transition temperature T g ≥620℃, softening temperature T f ≥680℃, the thermal expansion coefficient at 20~300℃ is (67~72)×10 -7 / ℃, has good anti-crystallization performance and acid resistance stability. Furthermore, the microchannel plate prepared from the leather glass has a baking temperature of ≥580℃ and a body resistance of ≤172MΩ.

[0047] According to a specific embodiment of the present invention, the weight ratio of the PbO to the Bi2O3 is 4 to 9: 1. Thus, the volume resistivity of the microchannel plate can be further adjusted to meet the preparation requirements of the microchannel plate.

[0048] According to a specific embodiment of the present invention, the weight ratio of the total content of PbO and Bi2O3 to the content of SiO2 is 1:0.3-0.9. This is conducive to the leather glass obtaining excellent anti-crystallization performance.

[0049] According to a specific embodiment of the present invention, the weight ratio of the content of Al2O3 to the total content of SiO2, Cs2O and Rb2O is 1:10 to 14. This is beneficial for the skin glass to obtain a higher secondary electron emission coefficient while optimizing its melting temperature and material properties, and preventing the skin glass's anti-crystallization performance and transition temperature from deteriorating.

[0050] According to a specific embodiment of the present invention, the weight ratio of the sum of the contents of SrO and Al2O3 to the content of SiO2 is 1:2 to 5. This is beneficial for the leather glass to obtain higher structural stability and chemical stability, while ensuring that the microchannel plate has a higher gain.

[0051] According to a specific embodiment of the present invention, the weight ratio of the total content of PbO and Bi2O3 to the content of SiO2 is 1:0.4-0.7. This is further conducive to the leather glass obtaining excellent anti-crystallization performance.

[0052] According to a specific embodiment of the present invention, the weight ratio of the content of Al2O3 to the sum of the content of SiO2, Cs2O and Rb2O is 1:10 to 12. This is further beneficial for the skin glass to obtain a higher secondary electron emission coefficient while optimizing its melting temperature and material properties, and preventing the anti-crystallization performance and transition temperature of the skin glass from deteriorating.

[0053] According to a specific embodiment of the present invention, the weight ratio of the sum of the contents of SrO and Al2O3 to the content of SiO2 is 1:3 to 4. This further helps the leather glass to obtain higher structural stability and chemical stability, while ensuring that the microchannel plate has a higher gain.

[0054] According to a specific embodiment of the present invention, the leather glass further comprises a clarifier.

[0055] According to a specific embodiment of the present invention, the content of the clarifier is 0.1-0.3 wt%.

[0056] According to a specific embodiment of the present invention, the clarifier is Sb2O3 and / or As2O3.

[0057] In the present invention, a clarifier is added to the skin glass component, and the content of the clarifier is controlled within the range of 0.1-0.3wt%, so as to be more conducive to the clarification and homogenization of the glass during the preparation of the skin glass.

[0058] A second aspect of the present invention provides a method for preparing leather glass, which comprises the following steps:

[0059] (1) first melting raw materials and a clarifier to obtain pre-sintered clinker glass, wherein the raw materials include SiO2, PbO, Bi2O3, Cs2O, Rb2O, BaO, MgO, Al2O3, ZrO2, Nb2O5 and SrO in terms of oxides;

[0060] (2) performing a second melting and clarification on the pre-sintered clinker glass to obtain sintered clinker glass;

[0061] (3) Extruding the sintered clinker glass to obtain a leather glass tube;

[0062] (4) Annealing the leather glass tube.

[0063] According to the present invention, the preparation of glass with a high softening point requires a higher melting temperature, and has requirements on the performance and stability of the heating equipment. At the same time, due to the short nature of the material, it is difficult to carry out conventional drawing and molding, and it must be formed by mechanical extrusion, which makes the processing difficult.

[0064] According to a specific embodiment of the present invention, raw materials (in terms of oxides, the raw materials include SiO2, PbO, Bi2O3, Cs2O, Rb2O, BaO, MgO, Al2O3, ZrO2, Nb2O5 and SrO) and a clarifier are subjected to a first melting, and the temperature of the first melting is 1300-1400°C. By controlling the temperature of the first melting within the above range and performing pre-melting, the volatilization of low-melting-point volatile components such as lead can be reduced, so that each oxide can obtain a corresponding melt through chemical reactions such as silicates, so as to obtain pre-sintered clinker glass.

[0065] According to a specific embodiment of the present invention, the pre-sintered clinker glass is subjected to a second melting and clarification, and the temperature of the second melting is 1550-1600°C. The second melting temperature is controlled within the above range for melting and clarification in order to achieve a more complete melting. Since high melting point oxides are added to increase the softening temperature, the required melting temperature must be higher. At this temperature, bubbles can be eliminated relatively well, and the sintered clinker glass with high composition consistency and no defects such as bubbles can be obtained.

[0066] In the present invention, the sintered clinker glass is extruded to obtain a skin glass tube, and the disadvantages of short properties and difficult forming of the directly drawn tube forming material are avoided through extrusion forming.

[0067] According to a specific embodiment of the present invention, in the annealing treatment of the leather glass tube, the heating rate of the annealing treatment is 2.5-4.0°C / min. Annealing is to eliminate stress. In the present invention, the heating rate of the annealing treatment is controlled within the above range, mainly to obtain a stress-free leather glass tube, to avoid the mechanical strength of the leather glass tube from being reduced, which causes it to be easily broken in the subsequent processing and MCP preparation process even if it is subjected to a small external force impact, and cannot be used normally.

[0068] According to a specific embodiment of the present invention, in the annealing treatment of the leather glass tube, the cooling rate of the annealing treatment is 0.5-1.5°C / h. In the present invention, the cooling rate of the annealing treatment is controlled within the above range, mainly to prevent the leather glass tube from staying in the annealing furnace for too long, causing deformation and loss of the original shape and size.

[0069] The third aspect of the present invention provides a microchannel plate, which includes the leather glass as described above, or the leather glass prepared by the preparation method as described above. Thus, the baking temperature of the microchannel plate can be effectively improved, and the ion feedback effect can be reduced, so that the baking temperature of the microchannel plate prepared by the leather glass is ≥580°C and the body resistance is ≤172MΩ.

[0070] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.

[0071] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.

[0072] Example

[0073] Example 1

[0074] Based on the oxides and their weight percentages in Table 1, frit glass and a microchannel plate (MCP) were prepared as follows.

[0075] (1) Preparation of leather glass: Mix the oxides according to the weight fractions in Table 1 and 0.2wt% Sb2O3, add them into a quartz crucible three times, melt them at 1350℃ for 4h, and obtain pre-sintered clinker glass; add the pre-sintered clinker glass into the crucible, heat it to 1575℃, melt and clarify it for 7h, and stir it with a stirring rod to obtain sintered clinker glass; cool the sintered clinker glass to 1500℃ and mechanically extrude it to obtain a leather glass tube with a wall thickness of 7-9mm; anneal the leather glass tube, heat it from room temperature to 600℃ and keep it for 4 hours, the heating rate is 3.25℃ / min, and then cool it to room temperature at a cooling rate of 1.0℃ / h. The annealed leather glass tube is subjected to secondary processing, and the inner wall of the glass tube is shaped by mechanical drilling and expanding, so as to realize the expansion processing of the inner wall of the glass tube. Then the outer circle of the glass tube is fixedly ground and polished by the inner wall to achieve external shaping, so as to obtain a glass tube with an inner diameter and wall thickness that meet the requirements.

[0076] (2) Preparation of microchannel plate (MCP): The skin glass tube obtained in step (1) is embedded in the core glass rod, and the single-filament and multi-filament are drawn. The multi-filament is regularly arranged and melt-pressed into a blank plate segment, which is then sliced, ground and polished to obtain a blank plate. The blank plate is corroded by nitric acid at a concentration of 1 M at 60°C, reduced with hydrogen, and plated with electrodes to obtain a microchannel plate.

[0077] Example 2

[0078] Example 2: A leather glass and a microchannel plate (MCP) were prepared according to the method of Example 1, except that the oxides and their weight percentages in Example 2 were as shown in Table 1, and 0.2 wt% of Sb2O3 was added as a clarifier.

[0079] Example 3

[0080] (1) Preparation of leather glass: Mix the oxides according to the weight fractions in Table 1 and 0.2wt% Sb2O3, add them into a quartz crucible three times, melt them at 1400℃ for 4h, and obtain pre-sintered clinker glass; add the pre-sintered clinker glass into the crucible, heat it to 1600℃, melt and clarify it for 7h, and stir it with a stirring rod to obtain sintered clinker glass; cool the sintered clinker glass to 1500℃ and mechanically extrude it to obtain a leather glass tube with a wall thickness of 7-9mm; anneal the leather glass tube, heat it from room temperature to 600℃ and keep it for 4 hours, the heating rate is 4.0℃ / min, and then cool it to room temperature at a cooling rate of 1.5℃ / h. The annealed leather glass tube is subjected to secondary processing, and the glass tube is internally shaped by mechanical drilling and expanding to achieve the expansion processing of the inner wall of the glass tube. Then the outer circle of the glass tube is fixedly ground and polished by the inner wall to achieve external shaping, so as to obtain a glass tube with an inner diameter and wall thickness that meet the requirements.

[0081] (2) Preparation of microchannel plate (MCP): The skin glass tube obtained in step (1) is embedded in the core glass rod, and the single-filament and multi-filament are drawn. The multi-filament is regularly arranged and melt-pressed into a blank plate segment, which is then sliced, ground and polished to obtain a blank plate. The blank plate is corroded by nitric acid at a concentration of 1 M at 60°C, reduced with hydrogen, and plated with electrodes to obtain a microchannel plate.

[0082] Example 4

[0083] Example 4: A leather glass and a microchannel plate (MCP) were prepared according to the method of Example 1, except that the oxides and their weight percentages in Example 4 were as shown in Table 1, and 0.2 wt% of Sb2O3 was added as a clarifier.

[0084] Example 5

[0085] Example 5: A leather glass and a microchannel plate (MCP) were prepared according to the method of Example 1, except that the oxides and their weight percentages in Example 5 were as shown in Table 1, and 0.1wt% Sb2O3 and 0.1wt% As2O3 were added as clarifiers.

[0086] Example 6

[0087] (1) Preparation of leather glass: Mix the oxides according to the weight fractions in Table 1 and 0.2wt% Sb2O3, add them into a quartz crucible three times, melt them at 1300℃ for 4h, and obtain pre-sintered clinker glass; add the pre-sintered clinker glass into the crucible, heat it to 1550℃, melt and clarify it for 7h, and stir it with a stirring rod to obtain sintered clinker glass; cool the sintered clinker glass to 1500℃ and mechanically extrude it to obtain a leather glass tube with a wall thickness of 7-9mm; anneal the leather glass tube, heat it from room temperature to 600℃ and keep it for 4 hours, the heating rate is 2.5℃ / min, and then cool it to room temperature at a cooling rate of 0.5℃ / h. The annealed leather glass tube is subjected to secondary processing, and the glass tube is internally shaped by mechanical drilling and expanding to achieve the expansion processing of the inner wall of the glass tube. Then the outer circle of the glass tube is fixedly ground and polished by the inner wall to achieve external shaping, so as to obtain a glass tube with an inner diameter and wall thickness that meet the requirements.

[0088] (2) Preparation of microchannel plate (MCP): The skin glass tube obtained in step (1) is embedded in the core glass rod, and the single-filament and multi-filament are drawn. The multi-filament is regularly arranged and melt-pressed into a blank plate segment, which is then sliced, ground and polished to obtain a blank plate. The blank plate is corroded by nitric acid at a concentration of 1 M at 60°C, reduced with hydrogen, and plated with electrodes to obtain a microchannel plate.

[0089] Table 1 Composition and content of leather glass

[0090]

[0091]

[0092] Comparative Examples 1 to 4

[0093] Based on the oxides and their weight percentages in Table 2, frit glass and microchannel plates (MCPs) were prepared as follows.

[0094] (1) Preparation of leather glass: Mix the oxides according to the weight fractions in Table 2 and 0.2wt% Sb2O3, add them into a quartz crucible three times, melt them at 1350℃ for 4h, and obtain pre-sintered clinker glass; add the pre-sintered clinker glass into the crucible, heat it to 1580℃, melt and clarify it for 7h, and stir it with a stirring rod to obtain sintered clinker glass; cool the sintered clinker glass to 1500℃ and mechanically extrude it to obtain a leather glass tube with a wall thickness of 7-9mm; anneal the leather glass tube, heat it from room temperature to 600℃ and keep it for 4 hours, the heating rate is 3.0℃ / min, and then cool it to room temperature at a cooling rate of 1.0℃ / h. The annealed leather glass tube is subjected to secondary processing, and the glass tube is internally shaped by mechanical drilling and expanding to achieve the expansion processing of the inner wall of the glass tube. Then the outer circle of the glass tube is fixedly ground and polished by the inner wall to achieve external shaping, so as to obtain a glass tube with an inner diameter and wall thickness that meet the requirements.

[0095] (2) Preparation of microchannel plate (MCP): The skin glass tube obtained in step (1) is embedded in the core glass rod, and the single-filament and multi-filament are drawn. The multi-filament is regularly arranged and melt-pressed into a blank plate segment, which is then sliced, ground and polished to obtain a blank plate. The blank plate is corroded by nitric acid at a concentration of 1 M at 60°C, reduced with hydrogen, and plated with electrodes to obtain a microchannel plate.

[0096] Table 2 Composition and content of leather glass

[0097]

[0098]

[0099] Test Case

[0100] Implementation of Test Examples 1 to 6

[0101] (1) Thermal expansion coefficient test

[0102] In the present invention, the leather glass obtained in Examples 1 to 6 was tested for thermal expansion coefficient using the GB / T7962.16-2010 colorless optical glass testing method. The test temperature was 300°C and the unit was ×10 -7 / ℃. The results are shown in Table 3.

[0103] (2) Acid resistance stability test

[0104] In the present invention, the leather glass obtained in Examples 1 to 6 was tested for acid resistance stability according to Part 14 of GB / T7962.14-2010, and its acid dissolution rate was less than 0.01 mg /

[0105] (cm 2 ×min), the acid resistance stability reaches level 1, and has good acid resistance. The results are shown in Table 3.

[0106] (3) Glass transition temperature T g and softening temperature T f test

[0107] In the present invention, the leather glass obtained in Examples 1 to 6 is tested for glass transition temperature T using the GB / T7962.16-2010 colorless optical glass testing method. g and softening temperature T f The results are shown in Table 3.

[0108] (4) Anti-crystallization performance test

[0109] In the present invention, the leather glass obtained in Examples 1 to 6 was tested according to the industry standard specified in JC / T 750-2014, and there was no crystallization or phase separation at 750 to 1100° C., and the glass had good anti-crystallization performance. The results are shown in Table 3.

[0110] (5) Baking temperature resistance test

[0111] In the present invention, the leather glass obtained in Examples 1 to 6 is further prepared into the baking resistance temperature of MCP, the unit is ° C. The specific test method is to use a vacuum oven to bake at a specific temperature for 120 minutes. The present invention takes 560 ° C as the starting point, sets the interval every 20 ° C, conducts a temperature increase test, and visually checks whether the MCP is deformed. The results are shown in Table 3.

[0112] (6) Body resistance test

[0113] In the present invention, the skin glass obtained in Examples 1 to 6 was further prepared into a volume resistance of MCP, in MΩ, and tested using GB / T37951-2019, with a reduction temperature of 520°C, a reduction time of 300 min, and a hydrogen flow rate of 0.3 L / min. The results are shown in Table 3.

[0114] Table 3

[0115]

[0116] Comparative test examples 1 to 4

[0117] In the present invention, comparative test examples 1 to 4 were carried out according to the methods of implementation test examples 1 to 6, and the specific results are shown in Table 4.

[0118] Table 4

[0119] Components Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 <![CDATA[Coefficient of thermal expansion at 300℃ / 10 -7 / ℃]]> 81.4 75.2 71.4 - Acid stability Level 1 Level 1 Level 1 - Glass transition temperature Tg / ℃ 598 577 636 - <![CDATA[Softening temperature T f / ℃]]> 655 630 704 - Anti-crystallization performance excellent excellent good Difference Baking resistance temperature / ℃ <560 <560 - - Volume resistance / MΩ 201 178 - -

[0120] Note: - indicates that the relevant data cannot be tested.

[0121] It can be seen from the test data of Examples 1 to 6 in Table 3 that the skin glass prepared by the present invention adds high softening point oxides ZrO2 and Nb2O5, which can maintain its expansion coefficient while increasing its softening temperature. Otherwise, it will be difficult to match a suitable core glass in the subsequent process. At the same time, it has high acid resistance and good anti-crystallization performance. Furthermore, the microchannel plate prepared with the skin glass has high resistance stability and high baking temperature resistance, and can be degassed by high-temperature baking to avoid ion feedback.

[0122] In the skin glass of Example 1, the total content of ZrO2 and Nb2O5 is 7% at the maximum, which makes it have excellent performance. Its thermal expansion coefficient at 300°C is 69.3×10 -7 / ℃, glass transition temperature T g The softening temperature is 646℃, T f It is 712°C, and has good anti-crystallization performance and acid resistance stability. Furthermore, the baking temperature of the microchannel plate prepared with the leather glass is 620°C, and the body resistance is 150MΩ, which effectively improves the baking temperature of the microchannel plate and effectively reduces its ion feedback effect.

[0123] In Comparative Example 1, Na2O and K2O are added to the leather glass, resulting in a low softening temperature, which makes it difficult to withstand high-temperature baking and cannot be degassed by high-temperature baking. At the same time, the cationic radius of the above-mentioned oxides is small, and it is easy to migrate and produce ion feedback, which cannot meet the performance requirements of the membraneless microchannel plate.

[0124] In Comparative Example 2, the total content of ZrO2 and Nb2O5 was reduced to 1%, resulting in a significant decrease in the softening temperature of the leather glass. f It is 630°C, which causes the baking resistance temperature of the microchannel plate to decrease, and the baking resistance temperature is less than 560°C.

[0125] In Comparative Example 3, the total content of PbO and Bi2O3 was reduced to 28%, resulting in a significant increase in the resistance value after reduction, which could not be measured using the testing equipment. At the same time, since the weight ratio of the total content of PbO and Bi2O3 to the content of SiO2 was not in the range of 1:0.3 to 0.9, the skin glass had poor anti-crystallization performance, and crystallization occurred during the wire drawing process, resulting in a decrease in material utilization, which brought considerable difficulty to the preparation of the microchannel plate.

[0126] In Comparative Example 4, the proportion of SrO was increased to 15%, and the clarification temperature required for the skin glass during the melting process was significantly increased, resulting in a significant increase in the difficulty of melting, and the anti-crystallization performance was very poor. There was obvious crystallization during the drawing process, which made it impossible to prepare the corresponding microchannel plate.

[0127] From the data of the above embodiments and comparative examples, it can be seen that the glass phase transition temperature Tg ≥620℃, softening temperature T f ≥680℃, the thermal expansion coefficient at 20~300℃ is (67~72)×10 -7 / ℃, it has good anti-crystallization performance and acid resistance stability. Furthermore, the baking temperature of the microchannel plate prepared from the leather glass is ≥580℃, and the body resistance is ≤172MΩ, which effectively improves the baking temperature of the microchannel plate and effectively reduces its ion feedback effect.

[0128] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.

[0129] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A leather glass, characterized in that: In terms of oxides, they include SiO2, PbO, Bi2O3, Cs2O, Rb2O, BaO, MgO, Al2O3, ZrO2, Nb2O5 and SrO; Among them, the content of SiO2 is 20-40wt%; the total content of PbO and Bi2O3 is 35-45wt%; the total content of Cs2O and Rb2O is 5-12wt%; the total content of BaO and MgO is 10-16wt%; the content of Al2O3 is 1-4wt%; the total content of ZrO2 and Nb2O5 is 3-7wt%; the content of SrO is 5-10wt%.

2. The leather glass according to claim 1, characterized in that: in, The content of SiO2 is 22-28wt%; the total content of PbO and Bi2O3 is 38-42wt%; the total content of Cs2O and Rb2O is 7-10wt%; the total content of BaO and MgO is 12-14wt%; the content of Al2O3 is 2-3wt%; the total content of ZrO2 and Nb2O5 is 3-6wt%; the content of SrO is 6-9wt%.

3. The leather glass according to claim 1, characterized in that: The weight ratio of the PbO to the Bi2O3 is 4 to 9:

1.

4. The leather glass according to any one of claims 1 to 3, characterized in that: The weight ratio of the total content of the PbO and the Bi2O3 to the content of the SiO2 is 1:0.3 to 0.

9.

5. The leather glass according to any one of claims 1 to 3, characterized in that: The weight ratio of the Al2O3 content to the total content of the SiO2, the Cs2O and the Rb2O is 1:10-14.

6. The leather glass according to any one of claims 1 to 3, characterized in that: The weight ratio of the total content of the SrO and the Al2O3 to the content of the SiO2 is 1:2-5.

7. A method for preparing leather glass, characterized in that: It includes the following steps: (1) first melting raw materials and a clarifier to obtain pre-sintered clinker glass, wherein the raw materials include SiO2, PbO, Bi2O3, Cs2O, Rb2O, BaO, MgO, Al2O3, ZrO2, Nb2O5 and SrO in terms of oxides; (2) performing a second melting and clarification on the pre-sintered clinker glass to obtain sintered clinker glass; (3) Extruding the sintered clinker glass to obtain a leather glass tube; (4) Annealing the leather glass tube.

8. The preparation method according to claim 7, characterized in that: In step (1), the first melting temperature is 1300-1400°C; In step (2), the second melting temperature is 1550-1600°C.

9. The preparation method according to claim 7, characterized in that: In step (4), the heating rate of the annealing treatment is 2.5 to 4.0°C / min; The cooling rate of the annealing treatment is 0.5-1.5°C / h.

10. A microchannel plate comprising a skin glass and a core glass, characterized in that: The skin glass is the skin glass described in any one of claims 1 to 6, or the skin glass prepared by the preparation method described in any one of claims 7 to 9.